HUBUNGAN KONFORMITAS DENGAN PERILAKU IMPULSIVE BUYING MELALUI TIKTOK SHOP PADA MAHASISWA DI KOTA MEDAN - Renny Amelia Sitanggang; Ervina Marimbun R. Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the relationship between conformity and impulsive buying behavior through TikTok Shop among university students in Medan City. The development of social media integrated with e-commerce services has transformed consumer behavior patterns, particularly among university students. Various features available on TikTok Shop, such as promotions, discounts, live shopping, and product recommendations, may encourage impulsive buying behavior. In addition, social pressure from peer groups through conformity is assumed to influence students' tendency to make unplanned purchases. This study employed a quantitative approach with a correlational research design. The research population consisted of university students in Medan City who use TikTok and have made purchases through TikTok Shop. The sampling technique used was purposive sampling, resulting in a total sample of 349 respondents. Data were collected using Likert-type psychological scales, namely the Conformity Scale based on the aspects proposed by Taylor, Peplau, and Sears (2009), and the Impulsive Buying Scale based on the aspects proposed by Verplanken and Herabadi (2001). The data were analyzed using correlation analysis to examine the relationship between the two variables. The research hypothesis states that there is a positive relationship between conformity and impulsive buying behavior through TikTok Shop among university students in Medan City. The findings of this study are expected to contribute to the development of social psychology and consumer psychology, as well as provide insights for university students to make wiser purchasing decisions in the digital era.